Transmission line fault analysis using actuating relays and Atmega 328P controller - Ambarapu Sudhakar; Gaddi Nagasai; Modala Prudhvi Sagar; Maya Vamshi; Vasala Nikhil; Bodapati Venkata Rajanna (International Journal of Applied Power Engineering (IJAPE), 2023)
Since transmission lines account for 80–86% of power system problems, protecting transmission lines is a critical concern. This research proposes a method to identify and categorize various short circuit defects on transmission lines. Various operational and fault circumstances on the transmission of high voltage lines, including L-L fault, single phase to earth fault, and double line fault, double line Three fault scenarios triple line fault, triple line to ground fault, and triple line are simulated using MATLAB software. These flaws damage the linked devices to the power grid. The main motto of this work is to analyze various kinds of faults and also to detect the type of the fault in transmission line. In order to simulate and evaluate the various faults, a 100 km transmission line model was created. A sim power system block library had a fault block, and the harmonic content of the various faults was studied using the FFT tool, the effect of faults was observed. Based on the analysis, a hardware model is designed to identify the faults in transmission line using actuating relays and Atmega 328P microcontroller and display the fault type and parameters like fault impedance, and distance at which fault occurred.